PENGAMANAN KOMPUTER JARINGAN LAN KAMPUS A UNIVERSITAS BINA DARMA BERDASARKAN LOG ROUTER - Irwansyah, Irwansyah (Universitas Bina Darma, 2013)
Bina Darma University is an institution that has intranet and internet networks are large. Computer networks are composed by a network that spread to several campuses. Each building will have space and laboratories. The number of intranet users who want to access the Internet will have an impact on network security, by increasing the number of deliveries virus, trojan or spam will be entered at the time of accessing the Internet network. In such conditions it is in this study make use of log router as a mechanism that is used to analyze network security at the University of Bina Darma. The scope of the discussion covers Laboratory Campus A. Based on the results of research and analysis, it can be concluded that there is still a lack of a PC to update the Operating System on a campus lab, or can be said to be very weak. Keywords: Internet Network, Log Router, Virus, Operating System